ORGANIZATION OF CLASSES ON LISTENING TO SAMPLES OF THE NATIONAL MAKOM IN PRIMARY SCHOOLS (Academia Science Repository, 2023)
The article discusses the importance of listening to music in introducing primary school students to the art of makom and educating the younger generation through the art of makom in the spirit of high human emotions.